Expression of heat shook protein 27 and proliferating cell nuclear antigen in human retinoblastoma - Qin, Dongju; Tan, Luosheng; You, Qinghua; Liu, Xiangping (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : This study aimed to observe the expressions of heat shock protein 27 (HSP27) and proliferating cell nuclear antigen (PCNA) in retinoblastoma (Rb) cells and to explore the relationships of the expression with Rb differentiation and optic nerve infiltration. Material and methods: Heat shock protein 27 and PCNA expressions in 36 routine Rb paraffin specimens were observed using PV9000 two-stage immunohistochemical staining. The correlations of the HSP27 and PCNA expressions with Rb differentiation and optic nerve infiltration were analyzed. Results: Heat shock protein 27 was weakly expressed in the normal retina, specifically in the ganglion cell layer. It was extensively expressed in Rb tissues at a positive rate of 69.4%, and the positive substances were primarily located in the cytoplasm. Proliferating cell nuclear antigen was expressed weakly or not at all expressed in the normal retina and was extensively expressed in Rb tissues at a positive rate of 83.3%, and the positive substances were primarily located in the nucleus. The positive expression rates of HSP27 and PCNA in the differentiated group were significantly higher than in the undifferentiated group (p < 0.05). The positive expression rates of HSP27 and PCNA in the optic nerve-infiltrated group were significantly higher than in the non-infiltrated group (p < 0.05). Heat shock protein 27 expression was positively correlated with PCNA expression in Rb (p < 0.01). Conclusions : Heat shock protein 27 and PCNA expressions are markedly correlated with cell differentiation and optic nerve infiltration in Rb.